Cinnamomum bejolghota Extract Inhibits Colorectal Cancer Cell Metastasis and TGF-β1-Induced Epithelial-Mesenchymal Transition via Smad and Non-Smad Signaling Pathway - Athicha Kittiwattanokhun; Sukanda Innajak; Etsu Tashiro; Masaya Imoto; Ramida Watanapokasin (MDPI AG, 2022)
Cinnamomum bejolghota, used in Thai traditional medicine remedies, has several biological activities including antimicrobial, antifungal, and anticancer. In colorectal cancer, epithelial-mesenchymal transition (EMT) is an initial step of cancer metastasis. Thus, this study investigated the effects of C. bejolghota bark extract (CBE) on colorectal cancer cell metastasis and transforming growth factor-β1 (TGF-β1) induced EMT in LoVo cells. The results showed that CBE could reduce cell migration, invasion, and adhesion of LoVo cells in a dose-dependent manner. In addition, our studies also showed that CBE could reverse TGF-β1-induced morphological changes as well as increase an epithelial marker, E-cadherin, while the expression of the mesenchymal marker, N-cadherin, was decreased in TGF-β1-treated LoVo cells. MMP-2 expression was effectively decreased but TIMP-1 and TIMP-2 expression was increased by the CBE treatment in LoVo cells. CBE also inhibited Smad2/3 phosphorylation and nuclear translocation as well as decreased the expression of Snail, Slug, and TCF8/ZEB1 transcription factors in LoVo cells. Moreover, CBE could inhibit TGF-β1-induced Smad-independent signaling pathway by decreased phosphorylation of ERK1/2, p38, and Akt. These findings suggest that CBE inhibited TGF-β1-induced EMT in LoVo cells via both Smad-dependent and Smad-independent pathways. Therefore, CBE may function as an alternative therapeutic treatment for colorectal cancer metastasis.